Mapping the Changing Governance Control Paradigms of Public Universities - Christopher, Joe (Virtus Interpress, 2013)
Drawing on a multi-theoretical approach to governance, interviews with chief audit executives of seven universities worldwide, and published literature, this study maps and demonstrates that as public universities shift from state controlled, public sector and collegial managerialism to corporate managerialism, they experience different range of controls to be monitored at the board, operational and assurance levels of governance. These differences suggest there is no one fit for governance policies of public universities. Instead, there is an onus on the board and management of each public university to identify their own particular multi-theoretical governance control paradigm. These findings have accountability implications for council members, senior management and control mechanisms such as external and internal audit.